2016
DOI: 10.4252/wjsc.v8.i8.251
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of germ cells into pluripotency

Abstract: Primordial germ cells (PGCs) are precursors of all gametes, and represent the founder cells of the germline. Although developmental potency is restricted to germ-lineage cells, PGCs can be reprogrammed into a pluripotent state. Specifically, PGCs give rise to germ cell tumors, such as testicular teratomas, in vivo , and to pluripotent stem cells known as embryonic germ cells in vitro . In this review, we highlight the current knowledge on signaling pathways, transcriptional controls, and post-transcriptional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 94 publications
(108 reference statements)
0
11
0
Order By: Relevance
“…This outcome shows that various mechanisms can synergize their effects in the reprogramming of PGCs. It has also been reported that mutations in genes involved in PGC development, such as Dnd1, Pten, and Pgct1, improve EGC derivation efficiency [19].…”
Section: Non-classical Pgc Reprogrammingmentioning
confidence: 98%
See 3 more Smart Citations
“…This outcome shows that various mechanisms can synergize their effects in the reprogramming of PGCs. It has also been reported that mutations in genes involved in PGC development, such as Dnd1, Pten, and Pgct1, improve EGC derivation efficiency [19].…”
Section: Non-classical Pgc Reprogrammingmentioning
confidence: 98%
“…The Kit signaling pathway can also be implicated in the origin of human ECCs. Both KIT and Kit ligand (stem cell factor) mutations are related to human teratomas [19].…”
Section: Pgc Reprogramming In Vivomentioning
confidence: 99%
See 2 more Smart Citations
“…This inter-relationship is of particular importance. Primordial germ cells are the precursors to all gametes as the founder cells of the germline, and can be reprogrammed into both pluipotent stem cells or germ cell tumors, such as testicular teratomas [140].…”
Section: Effects Of the Failure Of Exteriorization Of The Testes On Tmentioning
confidence: 99%